Thrombolytic therapy for mechanical aortic valve thrombosis in pregnancy: case report. Issue 12 (7th December 2022) - Nguyen, Khoa; Prasad, Pooja; Pare, Emmanuelle; Chadderdon, Scott; Khan, Abigail
Abstract: Background: Mechanical heart valves require long-term anticoagulation strategies to prevent valve thrombosis. Pregnant women with mechanical heart valves are especially susceptible to valve thrombosis, given their procoagulant state and the complexity of anticoagulation strategies during pregnancy. We describe a case of prosthetic valve thrombosis in a pregnant woman treated successfully with low-dose slow infusion of thrombolytic therapy. Case Summary: A 23-year-old pregnant woman with a mechanical aortic valve on subcutaneous enoxaparin presented to the maternal cardiac clinic for a follow-up visit. Her physical exam was notable for a loud grade three crescendo decrescendo murmur and follow-up transthoracic echocardiography revealed peak and mean gradients of 87 and 58 mmHg, respectively. The Doppler velocity index (DVI) was 0.24 with an acceleration time of 130 ms. Fluoroscopy confirmed a stuck leaflet disk. Thrombolysis was performed using a low-dose ultra-slow infusion of thrombolytic therapy (1 mg/h of tissue-type plasminogen activator) with the restoration of normal valve function after 8 days. A repeat transthoracic echocardiography showed a decrease in the peak and mean gradients to 37 and 21 mmHg, respectively, with an improvement in the DVI to 0.53. Repeat fluoroscopy confirmed the opening of both leaflet disks. Discussion: Treatment options for mechanical aortic valve thrombosis are either slow-infusion, low-dose thrombolytic therapy or emergency surgery. The hypercoagulable state of pregnancy makes adequate anticoagulation, proper monitoring, and medication adherence even more critical to prevent valve thrombosis. Physicians should educate pregnant patients on anticoagulation strategies and participate in shared decision-making.